Pergulatan Sosioreligius di Tengah Arus Perubahan Ekonomi pada Masyarakat Kampung Inggris Pare Kediri - Ahmad Subakir (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2018)
The establishment of educational institutes which mainly focus on English language course at Kampung Inggris (the Village of English) of Pare-Kediri plays pivotal role in the process of transformation of the local society especially in socio-religious and economic aspects they deal with. This article attempts to reveal socio-religious characteristic of the society at the Kampung Inggris along with their work ethos. The change of economic aspect has led to encounter of socio-religious aspect and the work ethos within the society as a result of the establishment of the English language courses coupled with the advent of outsiders who take the course. Employing socio-economic approach the study scrutinizes the dynamic of socio-religious aspect which grows as a consequence of the economic change. To get the necessary data and information, I use a panel of methods, which comprises interview, observation, and documentation. The discussion will focus on the socio-religious problems faced by the residents of the Kampung Inggris and their work ethos. The study finds that there has been a substantial change among the local society. The agrarian society at the Kampung Inggris has now transformed into capitalistic one. The transformation has subsequently affected their religious pattern from organic-religious to mechanic-religious.